2011
DOI: 10.1007/s00477-011-0523-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of transfer functions in statistical downscaling models for daily temperature and precipitation over Canada

Abstract: This study compares three linear models and one non-linear model, specifically multiple linear regression (MLR) with ordinary least squares (OLS) estimates, robust regression, ridge regression, and artificial neural networks (ANNs), to identify an appropriate transfer function in statistical downscaling (SD) models for the daily maximum and minimum temperatures (T max and T min ) and daily precipitation occurrence and amounts (P occ and P amount ). This comparison was made over twenty-five observation sites lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 53 publications
1
24
0
2
Order By: Relevance
“…Jeong et al . () compared ANNs with different transfer functions such as regression models for temperature downscaling and showed that multiple regression for monthly series performs better than an ANN except for the minimum temperature for which the ANN performs better.…”
Section: Introductionmentioning
confidence: 99%
“…Jeong et al . () compared ANNs with different transfer functions such as regression models for temperature downscaling and showed that multiple regression for monthly series performs better than an ANN except for the minimum temperature for which the ANN performs better.…”
Section: Introductionmentioning
confidence: 99%
“…In general MLP downscaling models give results similar to multiple linear regression downscaling methods for temperature and precipitation (Schoof & Pryor, 2001) and are capable of outscoring linear models when relationships are non-linear and/or interactive (Tang, Hsieh, Monahan, & Tangang, 2000). Nevertheless, there is no consensus on their performance versus linear models (Jeong, St-Hilaire, Ouarda, & Gachon, 2012b). For example, when downscaling temperatures over Europe, Huth et al (2008) concluded that non-linear methods were not an improvement over linear methods.…”
Section: Evaluation Of Linear and Non-linear Downscaling Methods Inmentioning
confidence: 94%
“…Because we are interested in downscaling temperatures in southern Ontario and Quebec, Canada, and we have the same reanalysis data available that Jeong et al (2012b) interpolated to the AOGCM (CGCM3.1) grid, it is natural for us to use the predictors recommended by Jeong et al (2012a). In particular, Jeong et al (2012a) mentioned that their predictor sets " … should be relevant to project anticipated predictand variables because they include sensitive predictors for future climate signal and variability such as temperature at 2 m, specific humidities at 500 hPa, 850 hPa and 1000 hPa, and 500 hPa and 850 hPa geopotential heights."…”
Section: Datasets a Predictorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion of altitude improved the predictions considerably. Jeong et al (2012) aimed at modelling daily temperatures and precipitation using covariates and historical data. They compared multiple regression models, ordinary least squares estimates, robust regression, ridge regression and artificial neural networks to identify an appropriate transfer function in statistical downscaling models to capture daily precipitation occurrence and amounts.…”
Section: Introductionmentioning
confidence: 99%